Effectiveness of Online Learning using Virtual Class During The Covid-19 Pandemic - Margaretha Karolina Sagala; Rangga Firdaus; Bayu Saputra (Universitas Lampung, 2021)
The Covid-19 outbreak in several countries, including Indonesia, does not seem to have ended yet. This has prompted various parties to try to stop and prevent the spread of the Covid-19 virus. One way that the Indonesian government has taken to prevent the spread of the virus is to close all public facilities. Unila took part in stopping the spread of Covid-19. This study aims to map a picture of the effectiveness of online learning using Virtual Class (VClass) during the Covid-19 pandemic. Descriptive quantitative research focuses on the effectiveness of online learning. The population of this research is the students of PTI FKIP Unila. The sample used was 35 students who were selected using simple random sampling technique. The online learning questionnaire was used as a data collection instrument. Data were analyzed using descriptive statistics. The results showed that students rated online learning using VClass as very effective (2.9%), effective (34.3%), moderately effective (40%), and less effective (22.9%). To improve the quality of online learning, the online learning concept solutions by Unila Lecturers: (1) Reduce online assignments; (2) Adding learning videos; (3) Do not use the group assignment discussion method. Meanwhile, the solution for Unila's UPT TIK's Main Duties: (1) Repairing the VClass server; (2) Increase the max file size that can be sent; (3) Change the menu or appearance and make it an apk.Keywords: Effectiveness, Covid-19 Pandemic, Online Learning, Virtual ClassDOI: http://dx.doi.org/10.23960/jpvti.v3.i1.202104